Error correction method for non-uniform distribution radar system errors based on iterative nearest point - LI Pengfei, MENG Shengbo, LUO Zhishun (Zhihui kongzhi yu fangzhen)
Radar system error registration is a prerequisite and foundation for radar networking. For radars with long detection distances, their measurement errors in the detection space exhibit obvious non-uniform distribution characteristics, which causes traditional system error correction methods to be difficult to solve the error correction problem. In response to the non-uniform distribution characteristics of radar system errors, this paper proposes to divide the radar detection space into several small intervals, in each of which the system errors can be considered as a fixed value. At this time, the iterative closest point algorithm can be used to calculate the radar system error in each interval, and finally a system error compensation matrix is formed for the entire detection space, thereby achieving accurate correction of non-uniform distribution system errors. The effectiveness of the proposed method is verified by the experimental data.